The cooperative learning: Understanding and increasing the knowledge of the facilities design without a professor extra effort - C. Ferrera; J. Fernández; A.C. Marcos (Multidisciplinary Journal for Education, Social and Technological Sciences)
Lecturing has been prevailing in higher education. This teaching and learning model hinders the understanding of fundamental concepts in practical courses. The cooperative learning allows an improvement in the student’s achievements, attitudes and persistence. The main goal of this work is to implement the cooperative learning in the teaching of the design of industrial facilities. This methodology aims to solve part of the problems of recently graduate students when they undertake engineering projects lacking knowledge. Finally, the results of an end-of-course satisfaction survey, conducted to assess this experience, are also presented.